Worlding Sei Shônagon : The Pillow Book in Translation - Henitiuk, Valerie (Perspectives on translation., 2012)
Contained herein are forty-eight translations1 of what is arguably the single most famous passage in Japanese literature, namely the opening section of The Pillow Book, written around the turn of the eleventh century by a woman we know as Sei Shônagon. The languages represented, in entries dating from 1875 to the present day, are Bulgarian, Catalan, Croatian, Czech, Danish, Dutch, English, French, German, Italian, Romanian, Russian, Spanish and Turkish; two versions have also been provided in Chinese (with additional versions in modern Japanese appearing in Appendix III). Most of the translations have previously been available only in rare or hard to obtain sources, and are now brought together for the first time in an affordable and readily accessible format.